LTP3 contributes to disease susceptibility in Arabidopsis by enhancing abscisic acid (ABA) biosynthesis. (30th July 2015) - Gao, Shan; Guo, Wenya; Feng, Wen; Liu, Liang; Song, Xiaorui; Chen, Jian; Hou, Wei; Zhu, Hongxia; Tang, Saijun; Hu, Jian
Summary: Several plant lipid transfer proteins (LTPs) act positively in plant disease resistance. Here, we show that LTP3 (At5g59320), a pathogen and abscisic acid (ABA)‐induced gene, negatively regulates plant immunity in Arabidopsis . The overexpression of LTP3 ( LTP3 ‐OX) led to an enhanced susceptibility to virulent bacteria and compromised resistance to avirulent bacteria. On infection of LTP3 ‐OX plants with P seudomonas syringae pv. tomato, genes involved in ABA biosynthesis, NCED3 and AAO3, were highly induced, whereas salicylic acid (SA)‐related genes, ICS1 and PR1, were down‐regulated. Accordingly, in LTP3 ‐OX plants, we observed increased ABA levels and decreased SA levels relative to the wild‐type. We also showed that the LTP3 overexpression‐mediated enhanced susceptibility was partially dependent on AAO3 . Interestingly, loss of function of LTP3 ( ltp3‐1 ) did not affect ABA pathways, but resulted in PR1 gene induction and elevated SA levels, suggesting that LTP3 can negatively regulate SA in an ABA‐independent manner. However, a double mutant consisting of ltp3‐1 and silent LTP4 ( ltp3/ltp4 ) showed reduced susceptibility to P seudomonas and down‐regulation of ABA biosynthesis genes, suggesting that LTP3 acts in a redundant manner with its closest homologue LTP4 by modulating the ABA pathway. Taken together, our data show that LTP3 is a novel negative regulator of plant immunity which acts through the manipulation of the ABA–SA balance.